2016
DOI: 10.1371/journal.pone.0168292
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Boundary Edge Effects in the Western Carpathians: The Influence of Hunting on Large Carnivore Occupancy

Abstract: The conservation and management of wolves Canis lupus in the periphery of their distribution is challenging. Edges of wolf distribution are characterized by very few and intermittent occurrences of individuals, which are modulated by multiple factors affecting the overall population such as human-caused mortality, management targets and food availability. The knowledge of population dynamics in the edges becomes crucial when hunting takes place nearby the edges, which may preclude population expansion. Here, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…However, the Carpathian population lacks strong expansion trend, illustrated for example by the lack of reproduction in the Beskydy mountains (Kutal, Váňa, Suchomel, Chapron, & López‐Bao, ), in contrast to substantial expansion of the Central European population, illustrated by its establishment in western Poland (Nowak & Mysłajek, ; Nowak et al., ), northern Germany and northern region of Czech Republic, where a permanent pack (IDs 2–8) was ascertained for the first time since 1766 (Flousek et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the Carpathian population lacks strong expansion trend, illustrated for example by the lack of reproduction in the Beskydy mountains (Kutal, Váňa, Suchomel, Chapron, & López‐Bao, ), in contrast to substantial expansion of the Central European population, illustrated by its establishment in western Poland (Nowak & Mysłajek, ; Nowak et al., ), northern Germany and northern region of Czech Republic, where a permanent pack (IDs 2–8) was ascertained for the first time since 1766 (Flousek et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to environmental dispersal resistance, anthropogenic impact could play a role in wolf population recovery. Besides differences in management regimes in particular regions (Kutal et al., ; Nowak & Mysłajek, ), the role of landscape fragmentation in population biology and conservation is widely debated (Mortelliti, Amori, Capizzi, Rondinini, & Boitani, ). As expected (Munroe, Croissant, & York, ), our study depicts steep gradients in landscape fragmentation corresponding to patterns of socioeconomic drivers within Central Europe, resulting in increasing dispersal resistance and population disintegration towards highly fragmented regions in the west (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study performed in Beskydy, between Slovakia and the Czech Republic, showed that hunting acts as a reducer in the availability of food for carnivorous mammals, with particular emphasis on canines and felines (Kutal et al 2016). This study analyzed the population dynamics of great carnivores between 2003 and 2012 and concluded that variations in hunting practices and their influence on the disponibility of preys in different scenarios resulted in a considerable behavioral disparity among the predator populations studied.…”
Section: Hunting Practices and Environmental Impactsmentioning
confidence: 97%
“…They were delineated using a combined approach linking habitat suitability analyses and least-cost modelling [35]. As the study area can be characterised as the region of either permanent or sporadic occurrence of wolf and lynx [42,43], we combined the core habitat areas and wildlife corridors into one class and refer to them as the corridors throughout the paper.…”
Section: Input Datamentioning
confidence: 99%